Gendered Prejudice and the Racialized “Other”: An Enquiry into Shakespeare’s Othello (Integral Research, 2024)
At the heart of William Shakespeare’s Othello lies the Venetian gentry’s very public contempt for the non-European protagonist Othello, who is frequently referred to as the “moor”; immediately racializing him as an anathema to the polite society of Venice. Othello’s identity is the fulcrum around which the play revolves, as his confidant Iago often preys upon Othello’s internalized inferiority complex regarding his race to sow doubts about Desdemona’s infidelity; almost guiding Othello to believe that it is very likely that Desdemona is unfaithful to him because Othello lacks all the cultural sophistry and racial purity to fully satiate her mind. The sexual politics of the play is not just limited to Desdemona’s perceived unfaithfulness, but also to other female characters, who are suspected of debauchery by their husbands; such gross hetero-patriarchal assumptions about them are indicative of the sexual mores that belie the very foundations of the Venetian society. Into such a scenario of distrust and suspicion, the racialization of Othello disrupts the binary constructs of good vs. evil, as his actions are often muddied by his inability to dispel the doubts surrounding his wife which severely undermines his leadership capabilities. This paper argues that the racialization of Othello and the sexual hypocrisy of the male authoritarian figures about the women in their lives are issues that drive the plot forward and eventually bring the tragic hero’s downfall, culminating after a series of events endanger the marriage of Othello and Desdemona and put Venice’s integrity at risk. Theoretical framework includes feminism, gender criticism and critical race theory.
Keywords: Racialization, Othering, Infidelity, Gendered Politics, Subjectivity, Prejudice.